Robert Boyle's blasphemous thoughts and "Flashy Emanations": newly discovered evidence. Issue 5 (20th October 2019) - Hunter, Michael
ABSTRACT: This article presents a hitherto unknown document relating to Robert Boyle's concern with casuistry, in other words, with the analysis of matters on his conscience. It comprises an autograph manuscript that Boyle submitted to his casuistical mentor, Thomas Barlow, which is here published in full, and both this and Barlow's response are discussed in the course of the article. The opportunity is also taken to provide a more general assessment of Boyle's casuistical concerns and their significance, drawing on Boyle's contact in this connection not only with Barlow, but also with two other prominent ecclesiastics, Edward Stillingfleet and Gilbert Burnet.